After I'm gone - Lippman, Laura, 1959- (William Morrow, An Imprint of HarperCollinsPublishers, 2014)
When Felix Brewer meets Bernadette "Bambi" Gottschalk at a Valentine's Dance in 1959, he charms her with wild promises, some of which he actually keeps. Thanks to his lucrative--if not all legal--businesses, she and their three little girls live in luxury. But on the Fourth of July, 1976, Bambi's comfortable world implodes when Felix, newly convicted and facing prison, mysteriously vanishes. Though Bambi has no idea where her husband--or his money--might be, she suspects one woman does: his devoted young mistress, Julie. When Julie disappears ten years to the day after Felix went on the lam, everyone assumes she's left to join her old lover--until her remains are discovered in a secluded park.